2006
DOI: 10.1073/pnas.0508511103
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping hand-over-hand mechanism of single molecular motility of cytoplasmic dynein

Abstract: Structural differences between dynein and kinesin suggest a unique molecular mechanism of dynein motility. Measuring the mechanical properties of a single molecule of dynein is crucial for revealing the mechanisms underlying its movement. We measured the step size and force produced by single molecules of active cytoplasmic dynein by using an optical trap and fluorescence imaging with a high temporal resolution. The velocity of dynein movement, 800 nm͞s, is consistent with that reported in cells. The maximum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
275
7
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(333 citation statements)
references
References 31 publications
(51 reference statements)
38
275
7
3
Order By: Relevance
“…The remarkably great speed implies an involvement of the MT-based motor molecules, most likely the classical Kinesin-I and the cytoplasmic dynein for the plus-and the minus-end directed runs, respectively. Interestingly, the speed measured for both the plus (848 6 17 nm/s) and the minus end directed motions (975 6 25 nm/s) is as high as determined for the conventional kinesin (600-1800 nm/sec) [Vale et al, 1985;von Massow et al, 1989;Bohm et al, 1999] and cytoplasmic dynein (800-1250 nm/s) [Paschal et al, 1987;Toba et al, 2006] in vitro, and about twice as high as measured in early syncytial embryos during phase I (407 6 49 nm/s and 475 6 42 nm/s for plus and minus end, respectively) [Welte et al, 1998]. This suggests that the MT-based transport machinery during the stages of the fast ooplasmic streaming is, not surprisingly, in a fully activated state.…”
Section: The Drosophila Oocyte As An In Vivo Model System Of Motor-mementioning
confidence: 66%
“…The remarkably great speed implies an involvement of the MT-based motor molecules, most likely the classical Kinesin-I and the cytoplasmic dynein for the plus-and the minus-end directed runs, respectively. Interestingly, the speed measured for both the plus (848 6 17 nm/s) and the minus end directed motions (975 6 25 nm/s) is as high as determined for the conventional kinesin (600-1800 nm/sec) [Vale et al, 1985;von Massow et al, 1989;Bohm et al, 1999] and cytoplasmic dynein (800-1250 nm/s) [Paschal et al, 1987;Toba et al, 2006] in vitro, and about twice as high as measured in early syncytial embryos during phase I (407 6 49 nm/s and 475 6 42 nm/s for plus and minus end, respectively) [Welte et al, 1998]. This suggests that the MT-based transport machinery during the stages of the fast ooplasmic streaming is, not surprisingly, in a fully activated state.…”
Section: The Drosophila Oocyte As An In Vivo Model System Of Motor-mementioning
confidence: 66%
“…A more specialized version of the model further proposes that run lengths are determined by random detachment of engaged motors, promoted by this load. As mentioned above, in vitro molecular motor studies have shown that motor velocity depends on load [19][20][21] such that motors move faster when under less load. Further, there is evidence that when multiple motors work together under negligible opposing load, the catalytic rate of each individual motor is not altered [26].…”
Section: Force-velocity Relationship In Vivo: Survey Of Existing Resultsmentioning
confidence: 93%
“…For neuronal vesicle transport velocities were normalized on a per-run basis by the authors. For the general VENoM model to be viable, the FVCs obtained in this fashion should at least satisfy one wellestablished property of molecular motors: a decrease in load should correspond to an increase in velocity [19][20][21]. Figure 1 shows the various velocities as a function of the relative load per motor -the predicted in vivo FVC.…”
Section: Force-velocity Relationship In Vivo: Survey Of Existing Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Under a high load, the dynein dimers moved forwards in 8nm steps if plenty of ATP was available but larger steps were reported for small or zero loads. It is not yet clear whether the observed 16nm and 24nm steps were actually 2 or 3 × 8nm steps in rapid succession, since other groups [60,61] did not observe any steps longer than 8nm, or whether under some circumstances the stalk is flexible enough to swing up to 24nm between specific binding sites on tubulin dimers (Fig. 2).…”
Section: Dyneinmentioning
confidence: 94%